Standard superficial temporal artery-middle cerebral artery bypass surgery in hemodynamic cerebral ischemia: indication and technique - Vajkoczy, Peter; Horn, Peter; Schmiedek, Peter (Operative techniques in neurosurgery, 1999)
Over the last years, new evidence has accumulated suggesting that hemodynamic compromise plays a key role in the manifestation of focal ischemic deficits in a subgroup of patients with occlusive cerebrovascular disease. For these patients, who are characterized by hemodynamic cerebral ischemia, superficial temporal artery-middle cerebral artery (STA-MCA) bypass surgery may represent an effective means to augment cerebral perfusion and, thereby, to improve their hemodynamic status. With new lessons learned from modern imaging techniques and with the availability of advanced functional cerebral blood flow studies, however, the management of this distinct patient population has changed considerably over the past years. In the present article we highlight our algorithm for identifying patients who are likely to profit from STA-MCA bypass surgery and outline the technical details of the operative procedure, as well as their preoperative and postoperative management.